2021
DOI: 10.1097/pxr.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Influencing kinetic energy using ankle-foot orthoses to help improve walking after stroke: a pilot study

Abstract: Background: An ankle-foot orthosis with an oil damper (AFO-OD) may improve kinetics and kinematics for efficient walking after stroke. Yet it is unknown whether hemiplegic walking behaves like "inverted-pendulum" gait and how it is modulated by using AFO-ODs for efficiency.Objectives: This study examined whether the use of AFO-ODs improves the kinetics of total vertical ground reaction force (vGRF) and kinematics of vertical pelvic displacement (vPD) in different walking phases, and gait speed following stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A study has shown that the newly developed AFO with spring damper is superior to the PLS AFO in improving balance (68). Studies of AFO with an oil damper (AFO-OD) have suggested that AFO-OD might significantly improve ankle joint motor function and gait parameters in stroke patients (69,70). Another study conducted a gait analysis after rehabilitation with different AFOs.…”
Section: Orthotic Devices Involving the Hip Jointmentioning
confidence: 99%
“…A study has shown that the newly developed AFO with spring damper is superior to the PLS AFO in improving balance (68). Studies of AFO with an oil damper (AFO-OD) have suggested that AFO-OD might significantly improve ankle joint motor function and gait parameters in stroke patients (69,70). Another study conducted a gait analysis after rehabilitation with different AFOs.…”
Section: Orthotic Devices Involving the Hip Jointmentioning
confidence: 99%
“…Adjustment of the resistance of an AFO is commonly achieved by changing trimlines, components, or setting of orthotic joints to improve lower limb joint kinematics and kinetics in the sagittal plane during gait. 22,23 However, it remains unknown whether this adjustment would affect the knee adduction moments in the coronal plane and increase the risk for inappropriate medial joint loading and potential osteoarthritis. Investigating the effects of AFO plantarflexion resistance on the lower-limb joints in the coronal plane will provide new information to guide clinical decisions by clinicians and orthotists and improve clinical care for people who are poststroke.…”
Section: Introductionmentioning
confidence: 99%
“…In the article mentioned above, 1 the author has requested the following corrections:1. Another inclusion criteria has been added to the paragraph under Methods on page 514.…”
mentioning
confidence: 99%